ARIA-EAACI care pathways for allergen immunotherapy in respiratory allergy - Bousquet, Jean (2021)
Allergen immunotherapy (AIT), the gradually increasing repeated administration of high doses of allergens to allergic patients, offers the potential for immune tolerance against reactions to the natural exposures to specific allergens. AIT may lead to the long‐lasting remission of allergic symptoms and is the only disease‐modifying intervention in IgE‐mediated allergic respiratory diseases. [...]